Implementation singing method in learning arabic vocabulary at kindergarten b qur’an madani east belitung - Rizqi lu Alhaura; Nanda Pratama; Sukma Rahma Hadana; Eka Mahargiani Rokhma (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aiming for explore implementation method sing in learning vocabulary Arabic language at Kindergarten B Qur'an Madani Belitung Timur in the year 2024/2025 academic year . Arabic language education has role important in development character and understanding of religion for child age early . Method sing believed can make it easier student in memorize vocabulary Arabic . Research This use approach qualitative with method descriptive , involving observation , interviews , and documentation as technique data collection . Research results show that method sing effective in increase understanding and mastery vocabulary Arabic , creating atmosphere fun learning , and increase interest and motivation students . However , there are a number of obstacles , such as Arabic language is considered foreign , difficulties in memorizing , and limitations facilities . For overcome problem mentioned , it is suggested parental involvement , improvement teacher skills , and management effective class . Research This expected can give contribution in development method learning Arabic at the level park children and become reference for institution education other.